A scoping review of theories, models and frameworks used or proposed to evaluate knowledge mobilization strategies - Saliha Ziam; Sèverine Lanoue; Esther McSween-Cadieux; Mathieu-Joël Gervais; Julie Lane; Dina Gaid; Laura Justine Chouinard; Christian Dagenais; Valéry Ridde; Emmanuelle Jean; France Charles Fleury; Quan Nha Hong; et al. (BMC, 2024)
Abstract Background Evaluating knowledge mobilization strategies (KMb) presents challenges for organizations seeking to understand their impact to improve KMb effectiveness. Moreover, the large number of theories, models, and frameworks (TMFs) available can be confusing for users. Therefore, the purpose of this scoping review was to identify and describe the characteristics of TMFs that have been used or proposed in the literature to evaluate KMb strategies. Methods A scoping review methodology was used. Articles were identified through searches in electronic databases, previous reviews and reference lists of included articles. Titles, abstracts and full texts were screened in duplicate. Data were charted using a piloted data charting form. Data extracted included study characteristics, KMb characteristics, and TMFs used or proposed for KMb evaluation. An adapted version of Nilsen (Implement Sci 10:53, 2015) taxonomy and the Expert Recommendations for Implementing Change (ERIC) taxonomy (Powell et al. in Implement Sci 10:21, 2015) guided data synthesis. Results Of the 4763 search results, 505 were retrieved, and 88 articles were eligible for review. These consisted of 40 theoretical articles (45.5%), 44 empirical studies (50.0%) and four protocols (4.5%). The majority were published after 2010 (n = 70, 79.5%) and were health related (n = 71, 80.7%). Half of the studied KMb strategies were implemented in only four countries: Canada, Australia, the United States and the United Kingdom (n = 42, 47.7%). One-third used existing TMFs (n = 28, 31.8%). According to the adapted Nilsen taxonomy, process models (n = 34, 38.6%) and evaluation frameworks (n = 28, 31.8%) were the two most frequent types of TMFs used or proposed to evaluate KMb. According to the ERIC taxonomy, activities to "train and educate stakeholders" (n = 46, 52.3%) were the most common, followed by activities to "develop stakeholder interrelationships" (n = 23, 26.1%). Analysis of the TMFs identified revealed relevant factors of interest for the evaluation of KMb strategies, classified into four dimensions: context, process, effects and impacts. Conclusions This scoping review provides an overview of the many KMb TMFs used or proposed. The results provide insight into potential dimensions and components to be considered when assessing KMb strategies.